KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN LELE (Clarias sp.) PADA SALINITAS MEDIA YANG BERBEDA - Maru Hariati Friska Sitio; Dade Jubaedah; M. Syaifudin (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACT The research consisted of two phases, pre research and research phase. Pre research was carrried out to quantify the isoosmotic of Juvenile catfish by conductivity both on media and fish body which purpose to make  the curve of the correlation between salinity with conductivity. The research phase was the maintenance of Juvenile Catfish for 20 days to prove isoosmotic value to survival rate, growth and feed conversion. This research used a completely randomized design with 5 treatments and 3 replications. The treatments were media freshwater (control), 2 ppt (P1), 4 ppt (P2), 6 ppt (P3), 8 ppt (P4). The research value showed there was positive correlation between salinity and conductivity. The isoosmotic value for Juvenil Catfish was 5,893 mS/cm or 4,11 ppt salinity. Survival, growth and feed conversion ratio shows the results were not significantly different (P <0,05). Meanwhile, regression equation indicated salinity (X) that optimal for the maintenance of Juvenile Catfish ranging from 2,6 to 5,0 ppt. Keywords : Conductivity, Growth, Isoosmotic, Salinity, Survival rate